Komunikasi Orang Tua dan Pembentukan Kepribadian Anak - Manap Solihat (MediaTor)
Education is, essentially, a lifetime experience. Education begins as early as childhood, and family become an early place to start. Parent’s communication plays important role in education, especially in shaping children’s personality. The roles of parents their children education aren’t only limited on providing material resources needed to pay education cost. Parents also have to add and keep updating their knowledge continuously. The other key to strengthening education is by providing a healthy, harmonious, and safe environment for their children growth. This should be parents’ role, too, in shaping their children’s personality.